Level of awareness and satisfaction of rural and urban voters towards the Parish pastoral council for Responsible Voting (PPC-RV) a comparative study. - Malcampo, Rex Sucaldito
Elections have been viewed by the PPC-RV as the only process that a great number of people can participate in decision-making. As an electoral movement, one of its central objectives is to generate awareness of, and Christian involvement in the elections. The PPC-RV believes that equality involvement of an informed electorate is needed, so that elections will be meaningful. Thus it is important that an investigation be made on the effectiveness of the PPC-RV through the level of awareness and satisfaction of rural and urban voters regarding its existence and operations. The place of residence of the voters as well as their respective age, sex, family income and educational attainment may possibly exhibit different degrees of inlfluences. This study, therefore, seeks to compare the level of awareness and satisfaction of voters from rural and urban barangays. Given these objectives, a survey was conducted in the rural barangay of Cubay in Miagao and in urban barangay of Benedicto in the district of Jaro in Iloilo City with a total of 150 respondents. A questionnaire which contained awareness and satisfaction scales was used. These scales were drawn to elicit voters' awareness and satisfaction concerning the existence and operations of the PPC-RV. Generally, based on their mean scores in the awareness and satisfaction test, rural and urban voters are moderately aware and satisfied of the existence and operations of the PPC-RV. The same findings were also found when they are grouped according to their respective age, sex, family income and educational attainment. With exception only to the group of low educated urban voters who had constantly established a low level of awareness and satisfaction. Examining further their mean scores, rural voters are more aware and satisfied of the existence and operations of the PPC-RV. The statistical computations using the Analysis of Variance proved that there is a significant difference in the level of awareness and satisfaction of voters when grouped according to their place of residence. The Analysis of Variance also revealed that there is no significant difference in the level of awareness and satisfaction of voters when grouped according to their sex, family income, and educational attainment. With exception, however, to voters when grouped according to their age which showed a significant difference in their level of awareness and satisfaction. Likewise, the computations also found that there is no significant interaction between place of residence and other research variables such as age, sex, family income and educational attainment in their effect on the level of awareness and satisfaction of voters towards the existence and operations of the PPC-RV. With exception, however, to the research variable of sex which showed a significant interaction with place of residence in their effect on the level of satisfaction of voters. Hence, the level of awareness and satisfaction of rural and urban voters towards the existence and operations of the PPC-RV are affected mainly by their age and place of residence..